2020
DOI: 10.3390/app10020560
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Capacity and Antigenotoxic Effect of Hibiscus sabdariffa L. Extracts Obtained with Ultrasound-Assisted Extraction Process

Abstract: Hibiscus sabdariffa (Roselle) is in high demand worldwide due to its beneficial health properties owing to the polyphenols content, mainly in the flower calyx. The objective of this study was to find the best conditions (time and liquid: solid ratio) to extract polyphenols from Roselle using Ultrasound-Assisted Extraction (UAE) (40 kHz, 180 W), with ethanol how solvent; as well as determine the yield of phenols, anthocyanin, flavonoids, tannins, antioxidant activity (DPPH) and antigenotoxic effect (comet assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 52 publications
0
21
0
2
Order By: Relevance
“…The purple rice is highly valued, particularly among the health-conscious consumers as a functional compound for human health among everyday sources of carbohydrate [12]. In other staple food crops, anthocyanin has been reported in purple maize, a variety that is rarely consumed in comparison with other non-staple food crops such as Brassica, Solanaceous species, and some edible flowers [13][14][15][16]. Additionally, anthocyanin can be directly taken from the concentrate in capsules for convenience, but this can be quite expensive [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The purple rice is highly valued, particularly among the health-conscious consumers as a functional compound for human health among everyday sources of carbohydrate [12]. In other staple food crops, anthocyanin has been reported in purple maize, a variety that is rarely consumed in comparison with other non-staple food crops such as Brassica, Solanaceous species, and some edible flowers [13][14][15][16]. Additionally, anthocyanin can be directly taken from the concentrate in capsules for convenience, but this can be quite expensive [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Solvent polarity seems to play an important role in the extraction efficiency of phenols. As this study and others have shown, high polarity solvents such as methanol, ethanol, and water will be more efficient than non-polar ones [47]. Student s test was calculated between phenolic content and polarity (p = 0.057), and nonparametric test, Kruskal-Wallis was calculated (p = 0.497).…”
Section: Extract Composition Analysismentioning
confidence: 99%
“…The DNA fragment migration patterns were evaluated with a fluorescence microscope at a magnification of 40× and with an excitation filter of 420-490 nm. The Komet-5 image analysis software developed by Kinetic Imaging, Ltd. (Liverpool, UK) was attached to a CCD [50,51].…”
Section: Comet Assay (Antimutagenic Test)mentioning
confidence: 99%